Effect of Syrian Zeolite Ore, Magnesium and phosphorus Salts on reduce Volatilized ammonia during Poultry manure Composting (Latakia University Journal -Biological Sciences Series, 2024)
The objectives of this study was to evaluate the effect of zeolite, Magnesium and phosphorus mineral salts in reducing nitrogen loss during poultry manure composting. The research carried out in soil chemistry and soil fertility laboratories in agriculture Faculty at Tishreen University in 2021.The poultry manure composted in plastic containers in a temperature-controlled incubator. Volatilized ammonia, ammonium ions and total nitrogen contents measured over 120 days.Three treatments in addition to control executed: OM (Control= poultry manure without any amendments). OMZ treatment received 15% zeolite by weight. OMS represents treatment of magnesium and phosphorus mineral salts, where magnesium was added as magnesium sulfate, while phosphorus was used as triple superphosphate fertilizer. The salt sources added at a molar ratio of 10% of mole number of initial nitrogen in poultry manure. Mixture treatment between zeolite and mineral salts (OMZS) applied at the same rate mentioned before.Main achieved results: the proposed protocols contribute in reducing nitrogen loss during composting. Final total nitrogen content ​​ decreased about 30% of the initial nitrogen, where volatilized ammonia constitute about 68% of this loss, and represent 20% of the initial nitrogen value.Zeolite application to composting medium (OMZ) reduced ammonia volatilization by 12.9% compared to control (OM). This loss reached 20.4% in salts treatment (OMS), whereas it was 25% in mixture treatment (OMZS).  Application of zeolite, Mg and P salts increased total N in the final produced compost by5% -12%  and NH4-N content by 28.5%- 39% compared to control(OM) respectively Scanning electron microscopy showed Struvite mineral formation in the produced compost in salts treatment (OMS), this  contributed to save ammonia during composting.